Clinicopathological correlation and expression of PD-L1 in cervical carcinoma: An immunohistochemical study (Journal of Pathology of Nepal, 2024)
Background: Cervical cancer is the fourth most common cancer in women globally and the second leading cause of cancer deaths in India. Risk factors include HPV infection, smoking, long-term oral contraceptive use, early pregnancy, nulliparity, and multiple sexual partners. Programmed cell death-1/programmed cell death-ligand 1 (PD-1/PD-L1) inhibitors may improve outcomes in recurrent, persistent, or metastatic cervical cancer. This study aimed to determine the various histological types of cervical carcinoma, determine PD-L1 expression, correlate it with PDL1-positive TILs, and provide insight into clinicopathological parameters such as age, stage, etc.Materials and methods: This prospective cross-sectional study (July 2022–June 2023) analyzed 50 histopathologically confirmed cervical carcinoma cases at a tertiary care institute in India. The tumors were classified, graded, and subjected to PD-L1 immunohistochemistry.Results: Squamous cell carcinoma (SCC) was the most common type, followed by adenocarcinoma. PD-L1 positivity was observed in 36% of cases, predominantly in SCC (39.1%). Expression increased with tumor grade and stage (p = 0.046), while tumor-infiltrating lymphocytes decreased in poorly differentiated tumors, indicating reduced immune response. The study highlights the significance of PD-L1 expression in cervical carcinoma and suggests routine immunohistochemical testing to identify patients eligible for targeted therapy, facilitating personalized treatment approaches.Conclusions: The study highlights the significance of PD-L1 expression in cervical carcinoma and suggests routine immunohistochemical testing to identify patients eligible for targeted therapy, facilitating personalized treatment approaches.